2023
DOI: 10.1590/1806-9282.20221445
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary thrombophilia and low -molecular -weight heparin in women: useful determinants, including thyroid dysfunction, incorporating the management of treatment and outcomes of the entity

Abstract: OBJECTIVE: Our study purposed to examine the complex relationship between low-molecular-weight heparin therapy, multiple pregnancy determinants, and adverse pregnancy outcomes during the third trimester in women with inherited thrombophilia. METHODS: Patients were selected from a prospective cohort of 358 pregnant patients recruited between 2016 and 2018 at the Clinic for Obstetrics and Gynecology, University Clinical Centre of Serbia, Belgrade. RESULTS: Gestational age at delivery (β=-0.081, p=0.014), resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We have demonstrated that LMWH therapy was negatively associated with RiAu between the 36th and 38th gestational weeks (gw), recently published in Revista da Associação Médica Brasileira, Volume 69. Moreover, younger gestational age at delivery, higher D-dimer values, and higher RiAu values were associated with APO, and the LMWH therapy indirectly affected APO via RiAu between the 36th and 38th gw which leads us to believe that previous APO should also be included in the decision-making process for LMWH therapy introduction [2][3][4] . In addition, the data for that study had been obtained from the hospital's digital database, including comorbid conditions such as thyroid dysfunction.…”
Section: Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that LMWH therapy was negatively associated with RiAu between the 36th and 38th gestational weeks (gw), recently published in Revista da Associação Médica Brasileira, Volume 69. Moreover, younger gestational age at delivery, higher D-dimer values, and higher RiAu values were associated with APO, and the LMWH therapy indirectly affected APO via RiAu between the 36th and 38th gw which leads us to believe that previous APO should also be included in the decision-making process for LMWH therapy introduction [2][3][4] . In addition, the data for that study had been obtained from the hospital's digital database, including comorbid conditions such as thyroid dysfunction.…”
Section: Point Of Viewmentioning
confidence: 99%
“…In addition, the data for that study had been obtained from the hospital's digital database, including comorbid conditions such as thyroid dysfunction. The thyroid hormones such as L-thyroxine (3,5,3',5'-tetraiodothyronine, T4), and L-triiodothyronine (3,5,3'-triiodothyronine, T3) are known to be effective in reproductive functions in humans and animals by regulating the ovarian, uterine, and placental tissues and metabolism in thyroidology [2][3][4][5][6][7] . Nevertheless, in our previous study, the women with APO in their current pregnancy did not reveal significance compared to the ones without APO in their current pregnancy in terms of thyroid dysfunction [2][3][4][5] .…”
Section: Point Of Viewmentioning
confidence: 99%